Modelagem matemática da infiltração de água no solo e distribuição espacial de atributos físicos de um Latossolo argiloso sob sistemas de manejo - Roehrs, Simone Andreia (2017)
The inadequate use and management of the soil has raised questions about its quality and sustainability. A reflection of this situation is the concern with the soil water infiltration, since water is one of the main factors of production and great responsible for the grain yield cultures. Thus, this study aimed to show the behavior of accumulated infiltration in management systems through mathematical modeling. Also, with geostatistical analysis, verify the spatial variability of soil physical attributes through thematic maps of these attributes. The experiment was conducted in the experimental area of the Paraná Agronomic Institute (IAPAR), regional pole of Santa Tereza do Oeste, Paraná, Brazil. The soil is a clay Oxisol in which the water infiltration was evaluated in 29 treatments that consisted of management systems: traditional no tillage system, planted no tillage system, no tillage system with scarification and no-tillage system with quality cover species in consortium or not, termed "retrievers" of soil structure. A randomized experimental design was carried out, with treatments T1 (Pearl millet), T2 (Common oat), T3 (Dwarf pigeon pea), T4 (Black Oat), T5 (Tillage system whit soil scarification), T6 (Cereal rye), T7 (Black oat + cultivated radish), T8 (Crotalaria juncea), T9 (Pigeon pea), T10 (Crotalaria spectbilis), T11 (Tillage system with application of 3 t ha-1 of gypsum), T12 (Black oat + white lupine), T13 (Velvet bean), T14 (Black Oat + Garden Pea), T15, Control (Traditional tillage system). The treatments T1C, T2C, T3C, T4C, T7C, T8C, T9C, T10C, T11C, T12C, T13C, T14C, T15C represent the same treatments described with 3 passes of compactor roller, indicating treatments artificially compacted. For the spatial variability, the areas with the management systems were analyzed: T15 (Traditional tillage system), T11 (Tillage system with application of 3 t ha-1 of gypsum) and T5 (Tillage system whit soil scarification). The accumulated infiltration of water did not differ significantly at 5% of probability between treatments, only between rain intensities. The mathematical models of Kostiakov and Philip are suitable for measuring the infiltration of water accumulated in soils with the same characteristics. The analysis of spatial variability revealed spatial dependence between the data, with the planted no tillage system and no-tillage system with scarification, presenting higher values of soil density and lower volume of macropores.